Physical Characteristic of Glucose Syrup From Gracilaria sp. - Pramidanirwa, Intan Ramadhita; Rosida, Dedin Finatsiyatull (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
The growing gap between domestic sugar production and consumption in Indonesia suggests that there are alternative carbohydrate sources beyond sugarcane. Seaweed Gracilaria sp. represents a promising renewable biomass due to its high cellulose content; however, its rigid lignocellulosic matrix limits enzymatic conversion efficiency. This study examines the physical characteristics of glucose syrup produced from Gracilaria sp. via microwave-assisted inorganic salt pretreatment, followed by cellulolytic hydrolysis with Viscozyme® L. The glucose syrup was assessed for yield, ash content, and total dissolved solids (TDS) based on standard analytical protocols. The results indicate that the pretreatment successfully enhanced enzymatic accessibility, yielding glucose syrup with physical properties comparable to conventional sweeteners used in food applications. These findings highlight the potential of Gracilaria spp. as a sustainable raw material for sweetener production and reinforce the importance of physical characterisation as a determinant of product stability and compliance with food quality standards. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 14: Life Below Water